Optical fibre duplexer module - Abdullah, Mohammad Khazani; Abas, Ahmad Fauzi (2003)
An optical fibre duplexing module comprising a transmitting port (Tx) and a receiving port (Rx) , a first length (1) of optical fibre connecting the transmitting port (Tx) via an isolator (I) to means (C/S) for combining and splitting optical signals, a second length (2) of optical fibre connecting the receiving port (Rx) via an optical filter (TF), preferably a tunable filter, to the combining and splitting means (C/S), and a third length (3) of optical fibre connecting the combining and splitting means (C/S) to a common port (C).